The Oxford handbook of applied nonparametric and semiparametric econometrics and statistics - Racine, Jeffrey (Oxford handbooks in economics, 2014)
This volume, edited by Jeffrey Racine, Liangjun Su, and Aman Ullah, contains the latest research on nonparametric and semiparametric econometrics and statistics. Chapters by leading international econometricians and statisticians highlight the interface between econometrics and statistical methods for nonparametric and semiparametric procedures.